Cognitive Consequences of Faith in God Among Filipino Women - Obligacion, Freddie R. (Research in the social scientific study of religion, 1999)
Adopting a structural-cognitive framework, this study analyzed the impact of faith on the cognitive schemata of 620 Filipino women. Through structural equation modeling, this investigation demonstrated that strong faith in the Divine Providence generates sequelae of constructive cognitions, namely, a perception of personal control or self-efficacy, high self-esteem, and a strong propensity for self-improvement. Findings contradict literature contending that religious individuals who entrust themselves "in God’s hands" also relinquish control over their lives. Results also challenge the position that Catholicism has been initnical to the personal and societal well-being of Filipino women. The beneficial effects of religious convictions suggest the capacity of secular ideologies to tap motivational forces embedded in the cultural matrix. Further indicated is the need for development workers to establish effective linkages with religious sectors in the task of nation-building.